2018
DOI: 10.47385/cadunifoa.v12.n35.451
|View full text |Cite
|
Sign up to set email alerts
|

Educação Física Escolar, atividade física e qualidade de vida: a visão de alunos universitários

Abstract: Percebe-se que muitos jovens não conseguem atingir níveis aceitáveis de atividade física, sendo assim considerados sedentários, com diminuição dessa prática entre o fim da adolescência e o início da fase adulta se apresentando de forma mais evidente. Como tal, a presente pesquisa pretendeu investigar a percepção da disciplina Educação Física como agente promotor de hábitos de atividades físicas e as possíveis causas dos baixos níveis de sua prática. Para isso, realizou-se uma pesquisa descritiva e para a colet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In this study, the lower physical activity levels have been observed as recurrent in Brazilian students 5 and other places such as Ireland 17 and Slovenia 18 . A cause for this result may be related to the irregular participation of university students in physical education classes in primary education, which could contribute to the maintenance of physical activity levels in adult life 19,20 and the high demand for academic activities that hinder the practice of physical activity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the lower physical activity levels have been observed as recurrent in Brazilian students 5 and other places such as Ireland 17 and Slovenia 18 . A cause for this result may be related to the irregular participation of university students in physical education classes in primary education, which could contribute to the maintenance of physical activity levels in adult life 19,20 and the high demand for academic activities that hinder the practice of physical activity 21 .…”
Section: Discussionmentioning
confidence: 99%